Penerapan Pajak Terhadap Industri Film Di Masa Pandemi - Herio Mujitahid; Halim Al Hafizh (Universitas Pendidikan Ganesha, 2021)
Taxes are compulsory contributions to the state that are owed by individuals or entities that are compelling based on law, without receiving direct compensation and used for the state’s needs for the greatest prosperity of the people. Tax payments are used to finance state households so that the benefits are felt by the wider community or for the public interest. The film industry is a creative industry engaged in the media, arts and culture. Compared to other creative industry sectors, the film, video and photography industries have the highest creativity and knowledge capital, as forms of intangible assets. Effectiveness means that the goals that have been planned before can be achieved or in other words, the targets are achieved because of the activity process. With the existence of an open letter and protests by the film industry, it has resulted in the provision of relief and incentives from the finance minister for entertainment tax, especially for films.